Desenvolvimento de competências docentes nos cursos de graduação em Administração nas IES privadas do Estado do Rio de Janeiro - Oliveira, Danielle Almeida (2016)
The current marketing requirements and professionals also come to higher education, especially in private PEIs due to public policies of government of the last 20 years have eased the process of opening these, causing a sharp rise. The role of private PEIs in the current educational context is very important, because these institutions make up much of the manpower for the country. Another highlight is the demand for undergraduate courses in Business Administration, which is mainly due to the need of Brazilian organizations, consolidating the Administrator as indispensable to the economy and Brazilian society, glimpsing an extensive field of action and emerging job market for this professional. In this context, a key gear for the Administrator of the training process occurs is the teacher, sometimes a lonely trail path in the acquisition of skills to establish in the labor market and meet the students' demands. This study aimed to identify if the skills developed by teachers of undergraduate courses in Administration in private HEI occur formally or informally. The research was qualitative in nature, with subsequent application of the content analysis technique. For data collection semi-structured interviews were conducted. It was also necessary literature on the subject, so that could help explain the phenomenon studied. At the end is the presentation of the results: how teachers of undergraduate courses in Administration in private HEI develop their skills.